CELLULAR DOSE DISTRIBUTIONS OF INHALED RADON PROGENY AMONG DIFFERENT LOBES OF THE HUMAN LUNG. Issue 4 (16th January 2020) - Hofmann, Werner; Winkler-Heil, Renate
Abstract: Basal and secretory cell doses in the different lobes of the human lung following inhalation of short-lived radon progeny were calculated for a five-lobe asymmetric, stochastic lung model, considering the non-uniform ventilation of the lobes. Dose calculations for defined exposure conditions revealed that the upper lobes receive higher doses than the average bronchial dose for the whole lung, with the right upper lobe receiving the highest dose. The resulting inter-lobar distribution of cellular bronchial doses indicated that the non-uniform lung morphometry is the dominating factor, while non-uniform ventilation only slightly enhances the lobar differences. The comparison of average lobe-specific bronchial doses with the average bronchial dose for the whole lung allows the calculation of lobe-specific dose weighting factors, which can be used to convert average bronchial doses based on symmetric airway generation or bronchial compartment models to lobar bronchial doses.